Old Europe ages: Can it still prosper? - Axel Börsch-Supan; Alexander Ludwig (Asian Development Bank Institute (ADBI), 2009)
Population aging will be a major determinant of long-run economic development in industrial and developing countries. The extent of the demographic changes is dramatic in some countries and will deeply affect future labor, financial and goods markets. The expected strain on public budgets and especially social security has already received prominent attention, but aging poses many other economic challenges that threaten productivity and growth if they remain unaddressed. There is no shortage of policy proposals to address population aging. However, little is known about behavioral reactions, e.g., to pension and labor market reform. This paper sheds light on such reactions in three large Continental European countries. France, Germany, and Italy have large pay-as-you-go pension systems and vulnerable labor markets. At the same time, these countries show remarkable resistance against pension and labor market reform. Key issues taken up in this paper are interactions between pension and labor market policies, and the behavioral reactions to reform. Which behavioral reactions will strengthen, which will weaken reform policies? Can Old Europe prosper even if behavioral reactions counter current reform efforts?
Keywords: J11; J21; D13; E27; H55; F16; F21; 330; Bevölkerungsentwicklung; Alternde Bevölkerung; Soziale Sicherung; Gesetzliche Rentenversicherung; Umlageverfahren; Arbeitsmarkt; Rentenreform; Arbeitsmarktpolitik; Prognose; Deutschland; Italien; Frankreich